Isolation and Characterization of Stigmasterol from Fritillaria roylei - Gunpreet Kaur; Vikas Gupta; R G Singhal; Parveen Bansal (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2020)
Fritillaria roylei (Kshirakakoli) is the threatened species of “Ashtwarga” group suffers lot of confusion for identification & authentification in Ayurvedic system of medicine. Due to lack of natural sources and insufficient availability of kshirakakoli, chances of adulteration and substitution increases which in turn leads to loss of faith of people in herbal drugs. Thus for identification and differentiation, quality standardization and quality assurance of kshirakakoli containing herbal formulations there is a need to isolate chemical marker compound using advanced analytical techniques. The methanol extract of root samples of plant was prepared and phytochemical screening was performed. Marker compound was isolated from the extract using column chromatography. Single compound having Rf value 0.31 was isolated with TLC by using mobile phase n-hexane: ethyl acetate: formic acid (8:2:0.1 v/v/v) and purified by re-crystallization with methanol. Isolated compound was further characterized by using melting point and spectral analysis. The methanol extract was dark brown in color and showed the presence of steroids, amino acids and flavonoids. The isolated compound was found to be white crystalline powder with melting point range of 167-169°C. Spectral analysis confirmed the presence of Stigmasterol. In present study stigmasterol was isolated for the first time and can be used as chemical marker for identification and differentiation of the plant from its substitutes.